2010
DOI: 10.1016/j.jcrysgro.2010.08.052
|View full text |Cite
|
Sign up to set email alerts
|

MOCVD growth and optical properties of non-polar (11–20) a-plane GaN on (10–12) r-plane sapphire substrate

Abstract: a b s t r a c tNon-polar a-plane GaN film with crystalline quality and anisotropy improvement is grown by use of high temperature AlN/AlGaN buffer, which is directly deposited on r-plane sapphire by pulse flows. Compared to the a-plane GaN grown on AlN buffer, X-ray rocking curve analysis reveals a remarkable reduction in the full width at half maximum, both on-axis and off-axis. Atomic force microscopy image exhibits a fully coalesced pit-free surface morphology with low root-mean-square roughness ( $ 1.5 nm)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 27 publications
(36 reference statements)
0
6
0
Order By: Relevance
“…Outstanding performance has recently been reported for InGaN/GaN-based LEDs along c -plane orientation 1 , 2 . However, it is commonly known that growing LEDs along the c -plane results in high built-in spontaneous and piezoelectric polarization, which leads to the quantum confined Starks effect (QCSE) 3 6 . Therefore, several groups have expended considerable effort in growing epitaxial layers along nonpolar surfaces in the absence of piezoelectric and polarization fields.…”
Section: Introductionmentioning
confidence: 99%
“…Outstanding performance has recently been reported for InGaN/GaN-based LEDs along c -plane orientation 1 , 2 . However, it is commonly known that growing LEDs along the c -plane results in high built-in spontaneous and piezoelectric polarization, which leads to the quantum confined Starks effect (QCSE) 3 6 . Therefore, several groups have expended considerable effort in growing epitaxial layers along nonpolar surfaces in the absence of piezoelectric and polarization fields.…”
Section: Introductionmentioning
confidence: 99%
“…Pant et al reported the least mosaicity and compositional inhomogeneity, which could have led to an enhancement in crystal quality. Hence, XRC and RSM measurements should be further utilized to confirm the structural properties, whereby by Williamson-Hall plot analysis could be obtained via the use of off-axis XRC [71,76,77].…”
Section: Photoluminescencementioning
confidence: 99%
“…As for the structural properties, further analysis on off-axis XRC should be implemented to further investigate dislocation and defect increase/decrease and their correlation with the growth conditions. In addition, Williamson-Hall plot analysis can be achieved with the use of off-axis XRC along [1010] and [2020] [65,76,77]. Based on the screened articles, a few studies reported the use of off-axis XRC analysis.…”
Section: Characterizationmentioning
confidence: 99%
“…Photonic crystal enhanced solar cells aiming to enhance the efficiency of thin film solar cells by the mechanisms of optical path increase, light trapping, and optical impedance matching have been proposed and studied in the literature mostly for silicon and germanium materials [22,23]. Our group has been working on the growth of InGaN heterostructures [24][25][26]. Previously, we proposed a solar cell design, where the optical absorption from a thin InGaN active layer was enhanced by a photonic crystal etched into the top surface [27].…”
Section: Introductionmentioning
confidence: 99%